Pengembangan Model Ontologi Pada Domain Bimbingan Belajar - Noviyanti, Komang Kartika; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
The role of education is very influential in the quality of learners. Education has an important role in developing the skills and skills that shape the nation's proper character and civilization in context. However, the problem faced today is that the quality of students decreases , making the quality of human resources in terms of mindset. So, the dissemination of information about tutoring will help improve learning outcomes, to provide value to students to improve their abilities in accordance with the areas of their interest. For this reason, the construction of tutoring needs to use the concept of semantic ontology. The o ntology development method used is Methodology. This method is one method of building an ontology model that can be reused for ontologies built for further research. The tutoring ontology development Model produces 23 classes, 9 object properties, 8 data properties, and 71 individuals or instances in each class.  The ontology evaluation process by performing SPARQL queries also gives the corresponding results.